(untitled) (Social Science Review, 2023)
A social movement is a planned attempt by many individuals to influence or oppose certain significant aspects of society. They have impacted laws, regulations, and even political structures. Recently, it has been observed that both the mainstream media and new media play crucial roles in developing social movements.. The new media can accelerate the recruitment and mobilisation of social movements. It can influence and set the agenda concerning any movements for the traditional media. However, movements based on new media platforms could only sustain if they received the support of the mainstream media. This paper uses the Shahbagh movement as a case study to examine how mainstream and new media played a crucial role in bringing it to the public’s attention. This article argues that the Shahbagh movement has shown that new media can influence mainstream media’s agenda and the development of a social movement in Bangladesh. It contributed to accelerating the resource mobilisation and recruitment of the Shahbagh movement and made it the leading news for the traditional media. At the same time, this paper also examines how the Shahbagh movement lost its ability to be newsworthy. Social Science Review, Vol. 39(1), June 2022 Page 57-73